Accelerometry-based assessment of physical activity and sedentary behavior in adult survivors of childhood acute lymphoblastic leukemia and their healthy peers - Vyhlídal, Tomáš; Dygrýn, Jan; Hrubá, Jaroslava; Chmelík, František (Scientific reports, 2023)
Adult survivors of childhood acute lymphoblastic leukemia (ASALL) compose a specific group that faces an increased risk of experiencing late effects of their earlier treatment. Physical activity (PA) may be one of the appropriate means for preventing or minimizing the late effects of treatment. The main purpose of this study is to characterize device-measured PA and sedentary behavior (SB) among ASALL. The specific objective was to compare the movement behavior with a group recruited from the healthy population and to determine the degree of compliance with health recommendations for PA in the adult population. Twenty ASALL and 21 healthy control group (CG) members participated in the study. Participants were between 18 and 30 years old. Movement behavior was assessed for seven days using an Axivity AX3 accelerometer and a 24-h wearing protocol. Movement behavior was characterized by the amount of time spent in SB, light PA (LPA), moderate PA (MPA), and vigorous PA (VPA). There were no significant differences in movement behavior or compliance with PA recommendations between the ASALL and CG. During the week, the ASALL accumulated 711 min per day of SB vs. 636 min per day in the CG (p = 0.26); the ASALL had 186 min per day of LPA vs. 201 min per day in the CG (p = 0.47); the ASALL had 132 min per day of MPA vs. 147 min per day in the CG (p = 0.25); and the ASALL had 5 min per day of VPA vs. 4 min per day in the CG (p = 0.48). All research participants (ASALL and CG) met the PA recommendations of > 150 min per week for moderate PA. The results of our study suggest that ASALL, even after suffering from that disease in childhood, display comparable levels of PA and SB to their healthy peers. Both groups met the health recommendations for PA. The device-based monitoring of PA and SB should be an integral part of monitoring the late effects of treatment.
Keywords: Accelerometry; dospělí; Adolescent; mladý dospělý; Precursor Cell Lymphoblastic Leukemia-Lymphoma; Health Status; Sedentary Behavior; lidé; zdravotní stav; akutní lymfatická leukemie; cvičení; Young Adult; akcelerometrie; Exercise; mladiství; Adult; sedavý životní styl; Humans